Exploring the potential impact of adding upper limit single trigger MET thresholds to a paediatric early warning scoring tool at a tertiary children's hospital: a retrospective review - Steckle, Shawn; Fowler, Casey; Campbell, Victoria (Frontiers in Pediatrics, 2024)
Objective: To determine the impact of adding upper threshold vital sign triggers to digital CEWT on the number of MET alerts. Methods: De-identified vital set data from the ieMR was taken for all paediatric patients £16 years old in a tertiary Brisbane children's hospital over 12-months in 2022. Patients in the paediatric intensive care unit, post anaesthetic care unit or the emergency department were excluded as they would not trigger MET alerts in these locations. Microsoft Excel scripts were used to tabulate and graph the data to compare the number of MET alerts in the current system vs with proposed upper thresholds for HR, RR, SBP, and severe respiratory distress. Results: A total of 389352 vital sets were used for analysis after exclusions. Total cumulative MET alerts increased by 229% from 1707 to 5623. Number of increased alerts was inversely proportional to age group. Respiratory rate and systolic blood pressure were the vital signs most associated with increased alerts. The largest number of new alerts came from patients with lower CEWT scores. The largest proportional increase in alerts came from those with high CEWT scores. Conclusions: Adding upper threshold vital sign triggers to the digital CEWT leads to a substantial increase in MET alerts. The consequent workload is not justified given the lack of evidence to suggest a failure of the current CEWT system in recognising deteriorating patients.